Perception of campus community towards the application and practicality of campus farming in IIUM, Gombak - Yusoff, Norul Hafizah; Ghani, Nurfaezah; Ibrahim, Putri Haryati (2014)
Urban farming is one of the approaches done to achieve sustainable agriculture that is widely practiced by communities, especially around the rapid urbanization areas to address the environmental and economic issues. Various efforts have been made over the past few decades in commercializing urban farming to the international, national and local level. However, public contribution towards it is still low due to absence of awareness and support from communities in creating a greener environment although massive farming systems are available. The paper reviews and analyses the practicality of applying campus farming within institutional environment from the campus communities’ points of views. Questionnaire surveys, interviews and observations were carried out among 15 workers and 50 students in International Islamic University Malaysia (IIUM), Gombak campus. Findings revealed that majority of the respondents agreed that campus farming is suitable to be applied in IIUM campus. In addition, this study proved that conducting campus farming is beneficial in terms of environment, economy and social aspects. These show that campus farming has the potential to be conducted within campus environment which may also improve quality of life for campus community. Therefore, the application of campus farming within institutions area should be encouraged to achieve sustainable development. Based on the finding, this research suggests that suitable locations and several design recommendations should be considered in applying campus farming within IIUM Gombak campus.